Data on melanin production in B16F1 melanoma cells in the presence of emu oil - Ito, Minoru (Data Brief, 2016)
Here, we present data on the effects of emu oil, obtained from emu (Dromaius novaehollandiae) fat deposits, on melanogenesis in B16F1 murine melanoma cells. The cells were cultured in media containing different concentrations of emu oil, and the melanin content of these cells was measured using a microplate reader. Next, melanin content was measured for cells cultured with α-melanocyte-stimulating hormone. This article reports the different melanin contents as μg melanin/mg cellular protein, by using bar graphs with error bars. The present data imply that emu oil reduces the cellular melanin production.